RANCANG BANGUN SISTEM PPMS UV-IoT UNTUK EDUKASI KANKER KULIT DAN GELOMBANG ELEKTROMAGNETIK - Yudi Guntara; Rahmat Firman Septiyanto; Siti Nala Farihah (Charm Sains: Jurnal Pendidikan Fisika, 2025)
Physics learning often faces challenges in visualizing abstract concepts such as electromagnetic waves, especially ultraviolet (UV) light. This research aims to develop and test the feasibility of Physics Parameter Monitoring System (PPMs) of UV based on IoT as a medium for skin cancer education. The system consists of GUVA-S12SD sensor, DHT11, Wemos D1 ESP8266, and Blynk platform for real-time data visualization. The research used the Research and Development (R&D) method of the 4-D model (Define, Design, Develop, Disseminate). The feasibility test by experts showed that the LKPD scored 85.25% and the UV PPMs 80.75%, both in the very feasible category. Implementation on class XI students increased active participation (80%) and concept understanding (up 15%). The results showed that PPMs UV can be used in interactive learning, helping students understand the relationship between UV rays and skin cancer risk, and developing data analysis skills. However, limitations such as limited research coverage, short trial duration, and reliance on the paid Blynk platform potentially hinder accessibility. Therefore, further development could include improving the design of the tool, testing on a wider scale, and integrating auto-upgrading and data storage features to make it more effective in learning and environmental monitoring.